Numerical Analysis of Senggarang Embankment Constructed with Cement-CSP Stabilied Silty Clay - Nur Sakinah; Chan, Chee Ming (Progress in Engineering Application and Technology, 2021)
One of the common problems faced at embankment is water seepage. In this study, seepage happened at the inland area which causing floods and disrupted agriculture in the surroundings area. The objectives of this research are to analyze the seepage characteristics of Senggarang embankment constructed with cement-CSP-stabilised silty clay and to evaluate the load-bearing capacity of the cement-CSP-stabilised silty clay embankment with the ‘prescribed displacement approach’ This study involved numerical simulation with the usage of the PLAXIS 8 software. Embankment was simulated using clay soil while the foundation of the embankment was treated and untreated silty clay. Data parameters were collected from previous study. Different water level was applied to see the changes of pore pressure distribution which lead to instability of the embankment. As water level increase, the total displacement increase. Therefore, mixture of cement-CSP are one solution to reduce seepage problem that faced at Senggarang embankment.